2014
DOI: 10.3989/gya.035713
|View full text |Cite
|
Sign up to set email alerts
|

Olive oils from Algeria: Phenolic compounds, antioxidant and antibacterial activities

Abstract: SUMMARY:The phenolic compositions, antioxidant and antimicrobial activities against six bacteria of phenolic extracts of olive oil varieties from eleven Algerian varieties were investigated. The antioxidant activity was assessed by determining the scavenging effect on the DPPH and ABTS .+ radicals. The antimicrobial activity was measured as a zone of inhibition and minimum inhibitory concentration (MIC) on human harmful and foodborne pathogens. The results show that total phenols was significantly (p< 0.05) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
(28 reference statements)
2
7
0
Order By: Relevance
“…The phenolic compounds detected belonging to phenolic alcohols (hydroxytyrol, tyrosol), cinnamic acid derivatives (p-coumaric acid, ferulic acid) and flavonoids (luteolin and apigenin). These compound identified were in agreement with previous works studying the same cultivar (Bengana et al, 2013;Tamendjari et al, 2014). Two another important peaks were eluted at 36.6 and 36.9 min respectively between luteolin and apigenin and showing the same spectral behavior ( max 280 nm).…”
Section: Identification and Quantification Of "Chemlal" Evoo Phenolicsupporting
confidence: 91%
See 1 more Smart Citation
“…The phenolic compounds detected belonging to phenolic alcohols (hydroxytyrol, tyrosol), cinnamic acid derivatives (p-coumaric acid, ferulic acid) and flavonoids (luteolin and apigenin). These compound identified were in agreement with previous works studying the same cultivar (Bengana et al, 2013;Tamendjari et al, 2014). Two another important peaks were eluted at 36.6 and 36.9 min respectively between luteolin and apigenin and showing the same spectral behavior ( max 280 nm).…”
Section: Identification and Quantification Of "Chemlal" Evoo Phenolicsupporting
confidence: 91%
“…(oleuropein or ligstroside derivatives) which occur in these EVOO at 63-91 mg kg −1 of EVOO as found in the work of Bengana et al (2013) studying the same EVOO variety at different harvest dates. The phenolic alcohols fraction was higher than flavonoids one which is consistent with the finding of Bengana et al (2013), whereas the work of (Tamendjari et al, 2014) studying the same Algerian cultivars shows a different result. These observations support the effect of various factors such as geographical origin, ripening degree and extraction process on chemical profiles and EVOO phenolic compounds composition Bengana et al, 2013).…”
Section: Identification and Quantification Of "Chemlal" Evoo Phenolicsupporting
confidence: 90%
“…The mechanisms of antimicrobial activity of OLE are not completely understood. OLE and other compounds in olive oil interact with phosphatidylglycerol at the surface of the bacterial cell wall, and cause changes in the cytoplasmic membrane which could lead to the disruption of the cell envelope [12,13].…”
Section: Resultsmentioning
confidence: 99%
“…OLE plays an important role in the plant's defense against microbial pathogens and insects [11]. Although OLE is not classified as a sanitizer, previous studies have indicated antimicrobial activity of OLE on L. monocytogenes, S. aureus and several species of enterobacteria, among others [12,13]. The minimum inhibitory concentration (MIC) values reported for OLE on S. aureus varies from 0.0625 to 0.5 mg/mL for certified strains of the American Type Culture Collection (ATCC), and from 0.0312 to 0.250 mg/mL for clinical isolates [14].…”
Section: Introductionmentioning
confidence: 99%
“…The value for regular almond was 37.7 mg·kg −1 (Moayedi et al, 2011), which is much more inferior to the values found in this study. Wijeratne et al (2006) reported a total phenolic content of 8 mg (quercetin equiv·g −1 of ethanolic extract) in whole almond seed while Laincer et al (2014) found a level of 218.66 mg·kg −1 total phenolic contents present in olive oils from Algeria. Our results are in the range of these findings.…”
Section: Total Phenolic Contentmentioning
confidence: 99%